Iatrogenic obstruction of the aorta – a sequence of delayed, fatal complications after ‘off-label’ interventional persistent ductus arteriosus closure - Ireneusz Haponiuk; Konrad Paczkowski; Maciej Chojnicki; Radosław Jaworski (Videosurgery and Other Miniinvasive Techniques)
A 10-month-old girl was admitted to the Intensive Care Unit with the symptoms of critical cardiac decompensation. In the 3rd month of life, 3 kg bw, she underwent an interventional persistent ductus arteriosus (PDA) closure in a high-reference pediatric cardiology center. Echocardiography performed on admission showed myocardial injury, with poor contractility, mild pulmonary hypertension and severe stenosis of the isthmus of aorta. The girl was urgently referred for surgical removal with the use of extracorporeal circulation (ECC) and deep hypothermia circulatory arrest (DHCA) technique. In the 4th postoperative day (POD), she developed cardiovascular decompensation and died in the 7th POD due to circulatory arrest in the mechanism of refractory ventricular fibrillation. In autopsy there were found microscopic signs of apoptosis in parenchymal organs below iatrogenic ‘coarctation’, typical for chronic ischemia. In the segments proximal to iatrogenic aortic stenosis there were evident vascular changes characteristic for chronic severe arterial hypertension.